Mastering private equity : transformation via venture capital, minority investments & buyouts /: transformation via venture capital, minority investments & buyouts. ([2017]) - Zeisberger, Claudia, 1965-; Prahl, Michael, 1974-; White, Bowen, 1981-
No abstract available